Greenhouse gas emission assessment methods, data sources and reporting processes in Vietnam - Tri, V. P. D.; Trung, P. K.; Loi, N. T.; Ghosh, Surajit; Holmatov, Bunyod (Can Tho University, 2023)
Vietnam is both at risk from and contributing to climate change. The country is the 17th largest emitter of greenhouse gas (GHG) emissions globally, with emissions reaching around 300.4 MtCO2eq in 2020, increasing to 344 MtCO2eq in 2022, and is projected to further increase to 515.8 MtCO2eq in 2030. This report provides an overview of GHG emissions, assessment methods, data sources, and reporting processes in Vietnam with a focus on the agriculture, forestry, and other land use (AFOLU) sectors. The report comprises four chapters: Chapter 1 provides an overview of GHG emissions assessment methods for the AFOLU sector and data sources in Vietnam; Chapter 2 delves into the process of GHG emissions assessment; Chapter 3 focuses on reporting GHG emissions assessment in Vietnam; and Chapter 4 provides a summary of the findings. The report demonstrates that Vietnam has produced numerous detailed reports on GHG emissions, covering various sectors which reflects a comprehensive picture of efforts and challenges in mitigating climate change. The assessments and reports on GHG emissions have highlighted significant growth in emissions from various sources. The process of GHG emissions assessment and reporting ensures that Vietnam's GHG emissions reductions are monitored, periodically assessed, and verified. Therefore, it can provide reliable information for policymakers to improve policy frameworks for satisfying the goal of GHG emissions reduction in the future. These assessments are conducted under the guidance of the Ministry of Natural Resources and Environment, involving the participation of state management agencies under different ministries, and scientists. GHG emissions data at the national level is typically collected and managed by the Vietnam Environment Administration (VEA)1 , and GHG emissions data at the local level (province) is managed by the Department of Natural Resources and Environment in each province.